Representação arquivística: o papel do CIA e do CONARQ para o desenvolvimento de políticas de descrição - MARTINS, Wanessa Rodrigues (Universidade Federal do Pará, 2019)
The representation of information in Archival Science is understood as a process of organization consisting of several phases, among them: appraisal, classification and description. It focuses on representation focusing on the activity of archival description, since it recognizes that this, being a research activity and that seeks, in the detail of the content and the documentary context, represent the information contained in archives using research instruments, and needs to be appropriated by reality of the archives in the public and private scope of these. In this way, the purpose of this research is to verify the possibility of obtaining theoretical and methodological parameters, through the CIA (International Council of Archives) and CONARQ (National Council of Archives) with a view to proposing political guidelines of description. It has as specific objectives to analyze theoretically and conceptually the concept of description in Archivology; present the CIA and CONARQ, as well as their respective publications concerning the archival description and identify theoretical-conceptual and practical elements capable of subsidizing the creation of description policies in archives. Qualitative research, of a documentary nature and descriptive orientation, initiated by exploring the literature of the literature concerning the themes through books and databases, by the descriptors: "archival representation", "archival description", "standards of description", "policies archives” and the CONARQ and CIA websites. The results reveal a range of normative products and instructions that can provide support and support for the development of policy guidelines in file descriptions. It is concluded, according to the results, the archival description, seen from the perspective of information representation and underpinned by policies of archival description is a kind of facilitator for the organization and representation in files, and does not signify an end in itself.